Hot Processing–Potential for Application in the Beef Processing Industry (Kansas Agricultural Experiment Station Research Reports, 1980)
Three studies were conducted to evaluate the economics and quality of hot-processed beef. Study I compared two hot-processing techniques to conventional chilling and processing to determine efficiencies of energy, labor, and other resources. Substantial savings occurring with hot processing techniques include: 32 to 42% less energy need, significantly less cooler space requirement, eliminating the need to shroud carcasses, less labor, and reduced carcass shrinkage resulting in savings of 2.36 to 2.75 per head slaughtered. Study II compared the color and eating qualities of electrically stimulated and hot-processed beef with conventionally processed beef. Electrically stimulated and hot-boned loineye steaks were similar or superior to conventionally treated counterparts for shear force, taste panel, and color characteristics. However, electrically stimulated and hot boned inside round steaks were less tender ( though still acceptable ) than conventionally processed steaks. Color was similar for all treatments. Study III compared microbial aspects of hot-processed with conventionally processed beef, in an attempt to establish minimum chilling rates required to produce an acceptable hot-processed product. Beef that is hot processed 1 hr postmortem and vacuum packaged must be chilled to 21 C within 9 hr and then chilled to 2 C to be microbially acceptable. This is the minimum acceptable chilling rate, but more rapid chilling would be more desirable from a microbiological standpoint provided it does not toughen the product by such changes as cold shortening.
Keywords: beef cattle